Magnetic critical properties and basal-plane anisotropy of Sr2IrO4. (2nd March 2016) - Fruchter, L; Colson, D; Brouet, V
Abstract: The anisotropic magnetic properties of Sr2 IrO4 are investigated, using longitudinal and torque magnetometry. The critical scaling across of the longitudinal magnetization is that expected for the 2D XY universality class. Modeling the torque for a magnetic field in the basal plane, and taking into account all in-plane and out-of-plane magnetic couplings, we derive the effective fourfold anisotropy erg mol −1 . Although larger than for the cuprates, it is found to be too small to account for a significant departure from the isotropic 2D XY model. The in-plane torque also allows us to set an upper bound for the anisotropy of a field-induced shift of the antiferromagnetic ordering temperature.